Antimicrobial Activity and Molecular Docking of Benzoyl-N,N’-dialkylurea against Target Proteins in Microbial Cells - Diyah, Nuzul Wahyuning; Warsito, Gita Miranda; Isnaeni; Hidayati, Shabrina Wahyu (Universitas Muhammadiyah Surabaya, 2023)
This research aims to evaluate the antimicrobial activity of benzoyl dialkylurea derivatives to meet the global need for new antibiotic lead compounds. Four compounds were tested in vitro against Staphylococcus aureus, Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa, and Candida albicans by broth dilution method using ciprofloxacin and nystatin as standards. Docking simulations were performed to target essential proteins including DNA gyrase, FabH, RNA polymerase in bacterial cells and DHFR in C. albicans. BDMU, BEU1, BEU2, BEU3 exhibited antibacterial activity while BEU1 and BEU2 showed weak antifungal activity against C. albicans. The BDMU, BEU2, BEU3 considered promising growth inhibition against P. aeruginosa. In silico molecular docking on DNA gyrase from P. aeruginosa (PDB. 6M1S) was proposed as a model for mechanism of action in bacterial cells. The monobenzoyl of dialkylurea containing urea functionality with chloro-substituent at position-2 and 4 on aromatic rings were potential as lead compound to generate new antibacterial agent.